Psychology and art: exploring drawing as of interaction, counter reaction, and self-healing to traumatic experience - Masanat @ Meramat, Florene Ejot; Razali, Rosmidahanim; Rehman, Sana; Shanat, Musdi; Merman, Hairulnisak (Universiti Teknologi MARA, Perak, 2025)
This study examines the role of drawing as an interactive, counter-reactive, and self-healing medium for individuals navigating traumatic experiences. Building on the interdisciplinary integration of psychology and art, the research highlights how visual expression can serve as a nonverbal and therapeutic pathway for processing trauma. Unlike traditional talk-based therapy, which relies heavily on verbal articulation, drawing and other art-based practices provide a safe space for individuals, especially those with limited language or emotional vocabulary, to externalize, explore, and reorganize their experiences. The study was conducted via an online art therapy workshop organised by Universiti Teknologi MARA (UiTM) Perak Branch and the University of Gujranwala in Lahore, Pakistan. Participants participated in structured and semi-structured drawing exercises to promote emotional expression, increase self-awareness, and foster resilience. The results indicate that art therapy, primarily through drawing, allows participants to tap into repressed memories and emotions within a safe and supportive setting, which helps alleviate the psychological pressure related to direct verbal sharing. Through creative engagement, individuals developed effective coping strategies, increased their self-esteem, and improved their emotional regulation. This research reinforces existing literature by showing that art therapy not only alleviates immediate trauma symptoms but also nurtures long-term adaptive capacities for mental health recovery. Additionally, the research highlights how adaptable art therapy is for different age demographics and situations, positioning it as a beneficial addition to conventional mental health treatments. By framing drawing as an interaction, counter-reaction, and self-healing process, this paper contributes to a deeper understanding of how creative practices intersect with psychological well-being, offering an evidence-informed model for trauma recovery and holistic personal growth.